The Effect of Giving A Heating Lamp on Increasing the Body Temperature of Patients with Postoperative Shivering - Gevi Melliya Sari; Karisma Dwi Ana; Sylvie Puspita; Erfan Zitni Amrullah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Shivering is closely related to hypothermia and is one of the seriously problems in surgical patients that can hurt the patient's condition because it affects patient comfort and increases metabolic needs that cause cardiovascular complications. The causes of shivering are the temperature of the operating room, the extent of the surgical wound, age, body mass index, fluids, gender, type of anesthesia, and duration of surgery. The aim of this study was to determine the effect of giving a heating lamp on increasing the body temperature of patients with postoperative shivering. This study was a quantitative study with a pre-experimental design type one group pretest-posttest. The population in the survey was postoperative patients. The sample in this study amounted to 32 respondents using the accidental sampling technique. The instruments in this study were thermometers, heating lamps, and observation sheets. Data analysis used the Wilcoxon sign rank test with P <0.05. This study showed that the average body temperature of patients before being given a heating lamp was 35.10 C. After being given a heating lamp, the average patient temperature was 36.70C. The results of the statistical analysis test obtained a P value of 0.00, which means that there is an effect of providing a heating lamp on increasing the body temperature of patients with postoperative shivering. Postoperative shivering can be treated by minimizing heat loss during surgery with various mechanical interventions such as providing a heating lamp.